Caveolins: targeting pro-survival signaling in the heart and brain - Stary, Creed M.; Tsutsumi, Yasuo M.; Patel, Piyush M.; Head, Brian P.; Patel, Hemal H.; Roth, David M. (Frontiers in Physiology, 2012)
The present review discusses intracellular signaling moieties specific to membrane lipid rafts (MLRs) and the scaffolding proteins caveolin and introduces current data promoting their potential role in the treatment of pathologies of the heart and brain. MLRs are discreet microdomains of the plasma membrane enriched in gylcosphingolipids and cholesterol that concentrate and localize signaling molecules. Caveolin proteins are necessary for the formation of MLRs, and are responsible for coordinating signaling events by scaffolding and enriching numerous signaling moieties in close proximity. Specifically in the heart and brain, caveolins are necessary for the cytoprotective phenomenon termed ischemic and anesthetic preconditioning. Targeted overexpression of caveolin in the heart and brain leads to induction of multiple pro-survival and pro-growth signaling pathways; thus, caveolins represent a potential novel therapeutic target for cardaic and neurological pathologies.